Evaluación del comportamiento de tres variedades de rosas (Rosa sp.) a diferentes niveles de deshidratación en el proceso de tinturado del botón, Pedro Moncayo- Ecuador 2012 - Farinios Peñafiel, Edison Rommel (2012)
The study entitled "Evaluation of the behavior of three varieties of roses (Rosa sp.) at various levels of dehydration in the process of dyeing the pink button, Pedro Moncayo - Ecuador 2012.” has been done in a suitable room located in Tabacundo parish, Pedro Moncayo Canton, Pichincha Province. In the investigation we used a random design with a factorial arrangement 32 and Turkey 5% tests of significance of treatment, factors and interactions Besides 9 treatments were evaluated with 6 repetitions the treatments were the result of the interaction of factor levels variety (Vendela, polar star and Amelia) and the factor of dehydration (0 hours of dehydration, 18 hours of dehydration and 19 hours of dehydration), the variables evaluated were: Volume of solution of the dye absorbed, uniform percentage of dyed, percentage of damage stalks morphological the buttons dyed roses, percentage of waste after the dyeing process, length of leaves in the vase, length of the button of the rose in the vase and the relationship B/C of each one of the treatments.